Incidental findings in female pelvis MRI performed for gynaecological malignancies - Silvia Bottazzi; Roberta V. Ninkova; Luca Russo; Andrea Ponsiglione; Benedetta Gui; Daniela Demundo; Massimo Imbriaco; Aradhana M. Venkatesan; Evis Sala; Stephanie Nougaret; Lucia Manganaro; Stefania Rizzo (Insights into Imaging)
Abstract Incidental findings on female pelvic MRI present diagnostic challenges and may have significant clinical implications. Defined as abnormalities unrelated to the primary imaging indication, these findings have become increasingly prevalent with the expanded use of MRI in gynaecological practice. Standard gynaecological MRI protocols, incorporating T1- and T2-weighted sequences, diffusion-weighted imaging, and contrast-enhanced sequences, facilitate the characterisation of numerous extra-gynaecological abnormalities, ranging from benign to critical lesions. This review proposes a compartment-based approach for identifying extra-gynaecological findings, discussing their imaging characteristics and differential diagnoses. This approach may help radiologists systematically assess incidental findings, potentially improving the recognition of clinically relevant abnormalities and supporting timely clinical decision-making. Critical relevance statement Incidental extra-gynaecological findings on pelvic MRI can present significant diagnostic challenges. Systematic evaluation of incidental extra-gynaecological findings on pelvic MRI can improve radiologists’ awareness of clinically relevant abnormalities. Key Points Extra-gynaecological incidental findings on pelvic MRI are common and range from benign to malignant conditions. A compartment-based classification—dividing the female pelvis into anterior, lateral, posterior, musculoskeletal, and miscellaneous compartments—provides a systematic framework for interpretation. Thorough assessment of all MRI sequences, including large field-of-view images, may help identify clinically relevant incidental findings. Graphical Abstract